2020
DOI: 10.17159/2411-9717/1103/2020
|View full text |Cite
|
Sign up to set email alerts
|

A critical analysis of recent research into the prediction of flyrock and related issues resulting from surface blasting activities

Abstract: SYNOPSIS Since 2010, a number of researchers have investigated the development of new models to generate accurate predictions relating to the risks from flyrock. The purpose of this paper is to summarize and analyse these recent studies in order to determine the validity of the findings as a global solution. Recent publications have proposed a wide range of potential approaches and techniques to predict or investigate flyrock. Several authors have proposed viable solutions based on assumed causative parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…All calculations relating to the throw or travel distance of flyrock are theoretical, and, as noted by van der Walt and Spiteri (2020) 476 , Raina, Murthy and Soni (2015) 477 and Ghasemi, Sari and Ataei (2012) 478 , predictions of flyrock distance are not accurate and continue to confound explosives engineers and blasters for a variety of reasons:  Several authors have proposed viable solutions based on assumed causative parameters and their impact as actual flyrock distance are not scientific and are highly dependent on the scrutiny of the researcher. In order to present results that are objective and uncriticizable, an accurate, quantitative and objective method of measuring the travel distance of flyrock is required 479 .…”
Section: Predictions Of Flyrock Distance Not Accuratementioning
confidence: 99%
“…All calculations relating to the throw or travel distance of flyrock are theoretical, and, as noted by van der Walt and Spiteri (2020) 476 , Raina, Murthy and Soni (2015) 477 and Ghasemi, Sari and Ataei (2012) 478 , predictions of flyrock distance are not accurate and continue to confound explosives engineers and blasters for a variety of reasons:  Several authors have proposed viable solutions based on assumed causative parameters and their impact as actual flyrock distance are not scientific and are highly dependent on the scrutiny of the researcher. In order to present results that are objective and uncriticizable, an accurate, quantitative and objective method of measuring the travel distance of flyrock is required 479 .…”
Section: Predictions Of Flyrock Distance Not Accuratementioning
confidence: 99%
“…The approaches or techniques implemented in the recent studies are summarized in Figure 2 and were comprehensively analysed by van der Walt and Spiteri (2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These various studies proposed viable models for predicting and analyszing flyrock based on presumed causative parameters as inputs and their estimated impact on flyrock as weights assigned to each input. However, all of these papers concluded that the respective models were site-specific and could not be applied to other environments (van der Walt and Spiteri, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations